Barrier Removal from an Image Sequence using Edge Flow Technique - Pannalal, B; Srinivasa Reddy, Ande; Yadagiri, Nadipalli (International Journal of Computer Sciences and Engineering, 2025)
Photography as a line of work requires that the shooting of convinced scenes take place in outside location as well as inside location. The being thereof a glass window grill and light source creates complications during indoor scenes whereas the presence of fence mostly obstructs the outdoor scenes. Such visual barriers are often impossible to avoid just by changing the camera position. Outdated computational methods are still not robust enough to remove such barrier from images without difficulty. The Proposed approach computationally removes the obstruction and occluding contents from images.